El pueblo wayuu de la Guajira colombo-venezolana: un panorama de su cultura - Hostein, Nelly (2012)
This article describes the origin of the Wayuu, as well as their history through time. Wayuu culture is related to the environment in which they live. Their way of life, even in our times, is characterized by cultural way of resistance to the western world and the recovery of the traditions.